Pengembangan Media Pembelajaran Animasi Interaktif Berbasis Adobe Animate - Anggara, Rosich; Supardji, Supardji (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to develop an interactive animation learning media based on Adobe Animate which is designed to increase the effectiveness and involvement of students in the learning process. It combines visual, audio, and interactivity elements to create an engaging and immersive learning experience. The development results show that interactive animation learning media based on Adobe Animate is effective and feasible to use as a teaching tool. Interactive features, such as quizzes, simulations, and animated animations, have been proven to increase students' interest and understanding of the material. This media also provides flexibility for teachers in delivering material in an attractive and easy-to-understand manner. This development is expected to be an innovative alternative in supporting the digital learning process, especially in the era of technology-based education. Further research is needed to test the effectiveness of this medium on a wider scale and in a variety of subjects.